OPTIMIZING CREATIVE POETRY WRITING THROUGH THE PICTURE-TO-PICTURE METHOD : INTEGRATING LOCAL WISDOM IN MALAYSIAN ISLAMIC EDUCATION - Umar Susanto, Rudi; Ghufron, Syamsul; Kasiyun, Suharmono; Hartatik, Sri; Shabrina Meutia, Nur; Rahmaniah Aquariza, Novi (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
This community service activity aims to optimize the poetry writing creativity of students through the application of the Picture to Picture method combined with local wisdom values. The service was carried out at the Guidance Studio of the An-Nahdloh Islamic Boarding School, Selangor, Malaysia, on July 29, 2025. The method of implementation of the activity was a workshop that included providing materials, an introduction to the Picture to Picture method, poetry writing exercises, presentations of works, and reflections. The results of the activity showed that students were able to improve their creative writing skills by being more imaginative, communicative, and contextual. The poems produced were full of nuances of religiosity, Islamic boarding school life, and local Malay culture. Thus, the Picture to Picture method has proven effective in developing writing skills based on local wisdom and is suitable for implementation in various educational institutions.